Spominska plošča Francu Hočevarju - Razpet, Marko (Obzornik za matematiko in fiziko, 2009)
On June 20, 2009 a memorial tablet to mathematician Franc Hočevar at his birthplace in Metlika, Slovenia was unveiled. This article contains his short biography and work, and present some of his scientific publications.
Keywords: biografije; Hočevar, Franc Jožef; matematika; slovenski matematiki